Umowa cywilnoprawna jako podstawowa forma działania agencji rządowych w Polsce - Bieś-Srokosz, Paulina (Kwartalnik Prawa Publicznego, 2012)
Governmental agencies as specific bodies of public administration perform several duties and responsibilities, which are assigned to them under the provisions of binding law and refer mainly to public utility services. In order to perform these duties and responsibilities in a proper and efficient way public administration uses different forms originating in public as well in civil law. One of these forms is a contract. The main aim of this article is to survey several questions concerning the use of civil law contract by the public administration bodies, i.e. the notion and character of civil law contract in this specific context, the extent of contractual freedom on the side of public administration side. Furthermore the article presents and discusses some examples of the use of civil law contract in daily practice of governmental agencies in Poland.